Assessment of Effects of Maternal Age and Other Factors on Risk of Birth Defects in Zamfara State, Nigeria - A. Abdullahi; N. O. Lasisi (Journal of Applied Sciences and Environmental Management)
Birth defects have being a major public health challenge among the new born babies worldwide, particularly in developing countries including Nigeria and other Africa Countries. Consequently, the objective of this paper is to assess the Effects of Maternal Age and Other Factors on the Risk of Birth Defects in Zamfara State, Nigeria. The study examined the data collected for the presence of birth defects amongst the maternal age categories as following  year. The study used logistic regression analysis to analyze the data and the study found that in the reviewed the highest prevalence of birth defect is malnutrition which stood at 34 - 45% of pregnant women in Zamfara State which the highest among the birth defects in zamfara state. More so, the results from the data showed that the chance of birth defect is higher among age less than 20 year compared to maternal age between 20-29 year old and maternal age of more than 30 year (>30 year). It was also observed that maternal mother less than 20 years (<20 year) old have a 14 times greater odds of a birth defect than maternal more than 30 year (<30 year) old and maternal age between 20-29 year old have a 6 times greater odds of a birth defect than maternal age of more than 30 year (>30 year).